Consensus design of a NOD receptor leucine rich repeat domain with binding affinity for a muramyl dipeptide, a bacterial cell wall fragment. (17th April 2014) - Parker, Rachael; Mercedes‐Camacho, Ana; Grove, Tijana Z.
Abstract Repeat proteins have recently emerged as especially well‐suited alternative binding scaffolds due to their modular architecture and biophysical properties. Here we present the design of a scaffold based on the consensus sequence of the leucine rich repeat (LRR) domain of the NOD family of cytoplasmic innate immune system receptors. Consensus sequence design has emerged as a protein design tool to create de novo proteins that capture sequence‐structure relationships and interactions present in nature. The multiple sequence alignment of 311 individual LRRs, which are the putative ligand‐recognition domain in NOD proteins, resulted in a consensus sequence protein containing two internal and N‐ and C‐capping repeats named CLRR2. CLRR2 protein is a stable, monomeric, and cysteine free scaffold that without any affinity maturation displays micromolar binding to muramyl dipeptide, a bacterial cell wall fragment. To our knowledge, this is the first report of direct interaction of a NOD LRR with a physiologically relevant ligand.